(untitled) - Nadel, Estelle; Strout, Bethany; Savos, Sammy (New York, 2024)
"A heartrending graphic memoir about a young Jewish girl's fight for survival in Nazi occupied Poland, The Girl Who Sang illustrates the power of a brother's love, the kindness of strangers, and finding hope when facing the unimaginable."--
Keywords: Nadel, Estelle; Comic books, strips, etc; Nadel, Estelle; Cartoons and comics; Holocaust survivors; Cartoons and comics; Holocaust, Jewish (1939-1945); Cartoons and comics; Poland; Cartoons and comics; Cartoons and comics; Cartoons and comics; Holocaust, Jewish (1939-1945); United States; Hidden children (Holocaust); Hidden children (Holocaust); Poland; Comic books, strips, etc; Holocaust, Jewish (1939-1945); Comic books, strips, etc; Holocaust, Jewish (1939-1945); Comic books, strips, etc; Holocaust survivors; Comic books, strips, etc; Comic books, strips, etc; Biographies; Comics (Graphic works); Historical comics; Biographical comics